2017
DOI: 10.1186/s13287-017-0511-8
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-targeted genome editing of mesenchymal stem cell-derived therapies for type 1 diabetes: a path to clinical success?

Abstract: Due to their ease of isolation, differentiation capabilities, and immunomodulatory properties, the therapeutic potential of mesenchymal stem cells (MSCs) has been assessed in numerous pre-clinical and clinical settings. Currently, whole pancreas or islet transplantation is the only cure for people with type 1 diabetes (T1D) and, due to the autoimmune nature of the disease, MSCs have been utilised either natively or transdifferentiated into insulin-producing cells (IPCs) as an alternative treatment. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 50 publications
0
26
0
1
Order By: Relevance
“…The previous results indicated regression of induced diabetic degenerative changes by AMSCs therapy. This outcome was concomitant with Gerace et al (35), who documented that MSC interventions demonstrated improved T1DM outcomes through MSC migration to areas of pancreatic injury. In addition, MSCs modify the islet microenvironment to promote the survival and regeneration of surviving β cells and abrogate inherent autoimmunity against β cells.…”
Section: Discussionmentioning
confidence: 53%
“…The previous results indicated regression of induced diabetic degenerative changes by AMSCs therapy. This outcome was concomitant with Gerace et al (35), who documented that MSC interventions demonstrated improved T1DM outcomes through MSC migration to areas of pancreatic injury. In addition, MSCs modify the islet microenvironment to promote the survival and regeneration of surviving β cells and abrogate inherent autoimmunity against β cells.…”
Section: Discussionmentioning
confidence: 53%
“…It was proved that mesenchymal stem cells modify the tissue microenvironment and promote the survival and regeneration of beta cell mass which controls the glycemic state more efficiently [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Due to safety concern about dissemination of the gene vectors and their adverse side-effect in non-target sites, a direct injection of the expression vector was used less than an indirect injection of cells injection. Genetically modified cell transplantation technology has been widely applied to the research of gene therapy in vitro and in vivo for many human diseases, such as junctional epidermolysis bullosa [124], metastatic cancer [125], type 1 diabetes [126]. As mentioned above, the process of tissue regeneration is regulated spatialtemporally by a variety of cytokines.…”
Section: Transplantation Of Genetically Modified Cellsmentioning
confidence: 99%